Augmentable Multi-Vertebrated Modular Space Station Robot - Kurt, Serkan (ELSEVIER SCIENCE BV, 2015)
On space stations, movement capacity of the repairment with the space suits are very restricted and dangerous. Not only movement but also traveling from somewhere to somewhere is also difficult itself. With the help of multi-axis modular vertebrates the ability to access the places we want, high movement capacity, plug and play structured robot is designed. Robots height is increased at the intended amount with the basic addition of an independent vertebrae. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Vertebra; Space Station; Robot; Modular System; Business & Economics